2022
DOI: 10.3390/su142316128
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 Prediction Based on the CEEMDAN Algorithm and a Machine Learning Hybrid Model

Abstract: The current serious air pollution problem has become a closely investigated topic in people’s daily lives. If we want to provide a reasonable basis for haze prevention, then the prediction of PM2.5 concentrations becomes a crucial task. However, it is difficult to complete the task of PM2.5 concentration prediction using a single model; therefore, to address this problem, this paper proposes a fully adaptive noise ensemble empirical modal decomposition (CEEMDAN) algorithm combined with deep learning hybrid mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[ 81 ] 2021 Marrakesh, Morocco WT-CNN H/-/- 0.01 - 99.10 - Ban et al. [ 104 ] 2022 Hangzhou, China CEEMD-LSTM-BP-ARIMA D/S/T+1 4.55 3.66 - 0.79 M.A.A.A.-q et al. [ 105 ] 2021 Wuhan, China PSO-SMA-ANFIS H/S/T+1 22.39 17.50 16.83 0.51 …”
Section: Methods Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 81 ] 2021 Marrakesh, Morocco WT-CNN H/-/- 0.01 - 99.10 - Ban et al. [ 104 ] 2022 Hangzhou, China CEEMD-LSTM-BP-ARIMA D/S/T+1 4.55 3.66 - 0.79 M.A.A.A.-q et al. [ 105 ] 2021 Wuhan, China PSO-SMA-ANFIS H/S/T+1 22.39 17.50 16.83 0.51 …”
Section: Methods Reviewmentioning
confidence: 99%
“…Ban et al. [ 104 ] incorporated CEED, BP, LSTM, and ARIMA to build a comprehensive hybrid framework that considered multiple factors and scaled for air pollutant prediction and early warning. Liu et al.…”
Section: Methods Reviewmentioning
confidence: 99%
“…The experimental results indicated that LSTM outperformed traditional statistical forecasting methods [12]. The three gated units in LSTM can capture the dependency between time series data and improve LSTM's learning ability [13].…”
Section: Related Workmentioning
confidence: 96%
“…Experimental results clearly demonstrate that the predictive accuracy achieved by the mixed model significantly outperforms that of both individual and integrated benchmark models. Ban et al [ 11 ] used CEEMDAN for PM2.5 time series data and applied Long Short-Term Memory(LSTM), Back Propagation(BP), Autoregressive Integrated Moving Average Model(ARIMA), and Support Vector Machine(SVM) to each modal component to obtain a satisfactory integrated prediction model.…”
Section: Introductionmentioning
confidence: 99%